Isobavachalcone isolated from Psoralea corylifolia inhibits cell proliferation and induces apoptosis via inhibiting the AKT/GSK-3β/β-catenin pathway in colorectal cancer cells - Li Y; Qin X; Li P; Zhang H; Lin T; Miao Z; Ma S (Dove Medical Press, 2019)
Yanxi Li,1 Xiaoxue Qin,2 Penglei Li,1 Hao Zhang,1 Tao Lin,1 Ziwei Miao,2 Siping Ma11Department of Colorectal Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital and Institute, Shenyang, Liaoning, People’s Republic of China; 2Department of Developmental Cell Biology, Key Laboratory of Cell Biology, Ministry of Public Health, and Key Laboratory of Medical Cell Biology, Ministry of Education, China Medical University, Shenyang, Liaoning, People’s Republic of ChinaBackground: Colorectal cancer (CRC) is a common form of cancer associated with a high mortality rate and poor prognosis. Given the limited efficacy of current therapies for CRC, interest in novel therapeutic agents isolated from natural sources has increased. We studied the anticancer properties of isobavachalcone (IBC), a flavonoid isolated from the herb Psoralea corylifolia, which is used in traditional Chinese medicine, in an in vitro model of CRC.Materials and methods: Cell viability and growth of CRC cells were determined by Cell Counting Kit-8 and colony formation assays following treatment with varying concentrations of IBC, respectively. Apoptosis was examined by 4′,6-diamidino-2-phenylindole staining and flow cytometry with Annexin V/propidium iodide double staining. Western blot analysis was used to analyze expression of apoptosis-associated protein pathway and the AKT/GSK-3β/β-catenin signaling pathway.Results: Initial experiments showed that IBC inhibited proliferation and colony formation of human CRC cell lines in dose- and time-dependent manners. The antiproliferative effect of IBC resulted from induction of apoptosis, as evidenced by morphological changes in the nucleus, flow cytometry analysis, upregulation of cleaved caspase-3 and cleaved PARP, changes in the ratio of the anti-apoptotic protein Bcl-2 and the pro-apoptotic protein Bax, translocation of Bax from the cytosol to the mitochondria, and decreased expression of two inhibitors of apoptosis family proteins, XIAP, and survivin. Western blot analysis of signaling pathway proteins demonstrated that IBC downregulated Wnt/β-catenin signaling, which has previously been associated with CRC, by inhibiting the AKT/GSK-3β signaling pathway.Conclusion: This study demonstrated that IBC inhibited cell proliferation and induced apoptosis through inhibition of the AKT/GSK-3β/β-catenin pathway in CRC. These results suggest the potential of IBC as a novel therapeutic agent for the treatment of CRC.Keywords: colorectal cancer, isobavachalcone, apoptosis, AKT, GSK-3β, β-catenin signaling